The chloroalkaloid (−)-acutumine is biosynthesized via a Fe(II)- and 2-oxoglutarate-dependent halogenase in Menispermaceae plants - Colin Y. Kim (Nature Portfolio, 2020)
Halogenated plant natural products are rare and plant halogenation enzymes are thus far unknown. Here Kim et al. identify a dechloroacutumine halogenase from Common Moonseed that catalyzes the final chlorination step in the biosynthesis of acutumine, a chloroalkaloid with selective cytotoxicity to cultured T cells.